1998
DOI: 10.1159/000018925
|View full text |Cite
|
Sign up to set email alerts
|

Is the Use of Ecstasy and Hallucinogens Increasing?

Abstract: This report presents findings of a community survey of 3,021 adolescents and young adults aged 14–24 years in Munich, Germany, carried out to determine the prevalence of use and abuse of and dependence on ecstasy, amphetamines and hallucinogens. The response rate was 71%. Results: (1) In 1995, 4% of the male and 2.3% of the female respondents aged 14–24 reported the use of ecstasy. Ecstasy-related substances (amphetamines and chemically related substances) were reported by 3.6% of men and 1.6% of women. Halluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 11 publications
2
61
0
3
Order By: Relevance
“…There is some empirical evidence for cognitive deficits in light MDMA users Parrott and Lasky, 1998). Schuster et al (1998) assessed a random sample of 3000 German adolescents (14 -25 years old), 3% of whom had taken ecstasy, mostly on just a few occasions. Yet, despite comparatively light patterns of use, one-in-five of the ecstasy users reported MDMA-related problems, which were categorized as 'abuse or dependence'.…”
Section: Discussionmentioning
confidence: 99%
“…There is some empirical evidence for cognitive deficits in light MDMA users Parrott and Lasky, 1998). Schuster et al (1998) assessed a random sample of 3000 German adolescents (14 -25 years old), 3% of whom had taken ecstasy, mostly on just a few occasions. Yet, despite comparatively light patterns of use, one-in-five of the ecstasy users reported MDMA-related problems, which were categorized as 'abuse or dependence'.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, methamphetamine is the most widely available and used club drug (United Nations, 2003). Investigators in many different countries also have reported an increase in MDMA use, as well as MDMA-related deaths, particularly among young people (Cregg and Tracey, 1993;Landry, 2002;Raikos et al, 2002;Schifano et al, 2003;Schuster et al, 1998;Wilkins et al, 2003). In the United States, Patel et al (2004) reported a 400% relative increase in MDMA-related fatalities between 1999 and 2001.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to combat the increasing use of club drugs in the community, NIDA has established a Web site to provide scientific information about them-http://www.clubdrugs.org (Volkow, 2004). Similarly, many investigators in other countries have suggested that the use of such drugs has increased (Gross et al, 2002;Joe Laidler, 2005;Lua et al, 2003;Schuster et al, 1998), and that party attendees typically use multiple drugs (Barrett et al, 2005;Boys et al, 1997). To better gauge the extent of this drug use, we examine the prevalence rates, patterns, and correlates of club drug use among youths aged 16 to 23 in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Among casual ecstasy users, 20% reported ecstasy-related problems and met criteria for abuse or dependence (Schuster et al 1998).…”
mentioning
confidence: 99%